Penerapan Model Experiential Learning pada Materi Pencemaran Lingkungan untuk Meningkatkan Hasil Belajar Siswa Kelas VIIA SMPN Satu Atap 3 Tungkal Ulu: Application of the Experiential Learning Model to Environmental Pollution Material to Improve Student Learning Outcomes of Class VIIA SMPN Satu Atap 3 Tungkal Ulu - Shopyan Hadi; Risnita Risnita; Evita Anggereini (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
The learning activities at SMPN Satu Atap 3 Tungkal Ulu still lack in training students to be active in the learning process so that students' learning outcomes are not optimal. This study aims to improve student learning outcomes by applying the Experiential Learning model. This study also observes the atmosphere of the learning environment that helps the application of the Experiential Learning model in improving student learning outcomes. This type of research is Classroom Action Research (PTK) guided by the Kemmis and Mc Taggart model, which consists of planning, action, observation, and reflection stages. This study involved students of class VIIA SMPN Satu Atap 3 Tungkal Ulu. The data was collected employing observation sheets and analysis of learning outcomes tests. The results showed that the application of the Experiential Learning model could improve student learning outcomes. A comfortable, safe, and fun learning environment is also a determining factor for students to learn more actively, which will help improve student learning outcomes.